1990
DOI: 10.3181/00379727-195-43127
|View full text |Cite
|
Sign up to set email alerts
|

A Double Isotope Technique to Determine Regional Albumin Permeability: Effects of Anesthesia

Abstract: The transvascular leakage of albumin in various organs and tissues was studied with a double isotope technique in rats anesthetized with sodium pentobarbital, given intraperitoneally or intravenously, and in unanesthetized (conscious) rats. 125I-labeled albumin and 131I-labeled albumin were injected into the tail vein 1 hr apart. The albumin permeability index in tissues and organs is indicated by the local ratio (Xa/Ya)/(Xb/Yb), where (Xa/Ya) is the ratio of 125I/131I-albumin activities per g of tissue and (X… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
6
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 6 publications
1
6
0
Order By: Relevance
“…In non-FR groups, PI A values in control lung, heart, liver and kidney showed close agreement with previously reported values for non-septic rodents [12]. In the present study higher values in skin (14.5 compared with 2.0) and skeletal muscle (7.0 compared with 2.0) may be due to indirect effects of higher doses of sodium pentobarbitone (60 mg\kg compared with 35 mg\kg, intraperitoneal) on the circulation, or the possibility of a low-grade systemic inflammatory response due to surgical cannulation and mechanical ventilation.…”
Section: Discussionsupporting
confidence: 91%
“…In non-FR groups, PI A values in control lung, heart, liver and kidney showed close agreement with previously reported values for non-septic rodents [12]. In the present study higher values in skin (14.5 compared with 2.0) and skeletal muscle (7.0 compared with 2.0) may be due to indirect effects of higher doses of sodium pentobarbitone (60 mg\kg compared with 35 mg\kg, intraperitoneal) on the circulation, or the possibility of a low-grade systemic inflammatory response due to surgical cannulation and mechanical ventilation.…”
Section: Discussionsupporting
confidence: 91%
“…sodium pentobarbital on peritoneal capillaries (Simchon et al. ). Because the time courses of the HT and [Pr]p were independent of the studied group, it is believed that these two variables had no influence on the evolution of the ΔRIHP responses (Series 2 & 3) or on the evolution of the %ΔRoMBF responses (Series 3) to rmDIVE throughout the experiment.…”
Section: Discussionmentioning
confidence: 99%
“…The reduction had little impact on our measurements and was more likely explained by the four times removal of 100 -200 l blood samples followed by dilution of blood as a 0.9% NaCl solution was injected to replace the collected volume. Alternatively, it could be a result of the anesthesia because it previously has been shown that pentobarbital sodium could increase the leakage of albumin from plasma (38). The albumin concentration in plasma at 20 and 30 min was fairly stable with small variation between individuals (49 Ϯ 2 mg/ml).…”
Section: Discussionmentioning
confidence: 89%